Pelaksanaan Pendidikan Islam Non Formal Dalam Pembentukan Akhlak Anak Asuh Di Panti Asuhan Yatim Piatu Cabang Muhammadiyah Juwiring Klatentahun 2015/2016 - Purwono, M. Arif Dwi; , Dra. Chusniatun, M.Ag (2016)
The aim of this research is to know the implementation of non-formal education in shaping children's moral in Muhammadiyah orphanage of Juwiring District, Klaten, in 2015/2016. This research uses field researh with qualitative descriptive approach, which uses case study method. The methods of collecting the data are interview, observation, and documentation, while the analyze technique in this research isinductive analysis done by a researcher to leave for a place or space to gather evidence through the reviewers of the phenomenon and formulate theories This research result shows that: 1) The Muhammadiyah orphanage of Juwiring District, Klaten implements non-formal Islamic education. The implementation is concentrated on spiritual and discipline aspects by doing devinity or Islamic activity, such as taḥfīẓ Qur'an, tahajud praying, congregated five-time praying and shalat, healthy, neat, an orderly living education. 2) The morals that are formed in this orphanage are moral to Allah, which includes fivetime shalat tahajud praying and taḥfīẓQur'an, moral to other, which requires politeness to the mentor, not to underestimate and also respect every guest that comes to the orphanage, and moral to himherself by wearing clotes covering aurat. Covering clothes cithes inside or outside the orphanage. 3) Shaping morals of the children that stay overnigh In Muhammadiyah orphanage of Juwiring gives positive effects to them. It can be seen by their attitude, behavior, and speaking attitude. They even know how to act and the effects for them selves, eitherpositive or negative.